Cytotoxicity of Juniperus excels and Salvia mirzayanii Extracts against HepG2 Cells: Juniperus excels and Salvia mirzayanii cytotoxic effects - Soheila Khabbaz Azar; Mahmood Reza Moeen; Hossein Niknahad (Iranian Journal of Pharmaceutical Sciences, 2012)
In the recent decades, a lot of efforts have been directed for the discovery and production of anticancer agents. Plant kingdom is one of the main sources which has attracted the attention of investigators for finding new medicines including anticancer agents. In the present study, the cytotoxic effects of the extracts of five plants, native of Iran including Salvia mirzayanii, S. macrosiphon, S. multicaulis, Juniperus excels, and Peganum harmala, against HepG2 cell lines were investigated. Cytotoxicity was assessed by MTT test, and comparison of the IC50s revealed that the extracts of aerial parts of the J. excelsa had the strongest cytotoxic effects followed by S. mirzayanii, and the extract of the root of P. harmala with IC50s of 0.54, 1.52, and 2.50 mg/ml, respectively. The extracts of S. macrosiphon and S. multicaulis had no significant cytotoxic effects against HepG2 cells. The cytotoxic effects of J. excelsa is seemed to be due to ATP depletion as ATP levels of HepG2 cells incubated for 24 h with 0.5, and 0.7 mg/ml of the extracts of J. excelsa was decreased to 47% and 27% of control, respectively. The ATP depletion was timedependent and ATP was depleted before cytotoxicity ensued. Oxidative stress was not important in cytotoxicity of J. excelsa as lipid peroxidation and GSH depletion was not significantly different from control cells. However, cytotoxicity of S. mirzayanii was not accompanied by ATP depletion or oxidative stress. The exact mechanism(s) of cytotoxicity of these extracts needs further investigation.